Designing Sustainability for All The Design of Sustainable Product-Service Systems Applied to Distributed Economies - Vezzoli, Carlo; Garcia Parra, Brenda; Kohtala, Cindy (Lecture Notes in Mechanical Engineering, 2021)
This open access book introduces design for Sustainable Product-Service Systems (S.PSS) and for Sustainable Distributed Economies (S.DE). These are introduced as technical and operative tools for the development of a new generation of designers, responsible and capable of designing environmentally, socially and economically sustainable solutions, accessible to all. The book provides a comprehensive framework and also practical tools to support the system design for sustainability process. It overviews methodologies, tools and strategies for Sustainable PSS design applied to Distributed Economies (DE) and provides strategies and design guidelines. All of these are highlighted and expanded upon with international case studies.